2013
DOI: 10.5586/asbp.2012.042
|View full text |Cite
|
Sign up to set email alerts
|

Variability of alder-dominated forest vegetation along a latitudinal gradient in Slovakia

Abstract: Syntaxonmical revision of azonal forest vegetation with dominance of Alnus glutinosa and A. incana was done along a latitudinal transect of Slovakia. A data matrix consisting of 240 phytosociological relevés was obtained in accordance with the standard Zürich-Montpellier approach. Detrended correspondence analysis was used to clarify the relationships between the vegetation composition and environmental variables, whereas one-way ANOVA was applied to quantify the differences in site requireme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…pH values for the studied species ranged from 6 to 7, whereas soil nitrogen values ranged from 7 to 8. EIVs for soil N concentration and pH in the present study were similar to those reported for other swamp forests (Slezák et al, 2012). The studied species were indicators of weakly acid to weakly basic and indicated fertile soils with high bioactivity and alkaline and near neutral pH (Vallet et al, 2008).…”
Section: Discussionsupporting
confidence: 87%
“…pH values for the studied species ranged from 6 to 7, whereas soil nitrogen values ranged from 7 to 8. EIVs for soil N concentration and pH in the present study were similar to those reported for other swamp forests (Slezák et al, 2012). The studied species were indicators of weakly acid to weakly basic and indicated fertile soils with high bioactivity and alkaline and near neutral pH (Vallet et al, 2008).…”
Section: Discussionsupporting
confidence: 87%
“…This proposal, which was also adopted by Seibert (1992), highlighted the need of more complex analysis and most likely resulted from unclear relations between the Carici remotae-Fraxinetum excelsioris and group of syntaxa described from Carpathian region within a few years of each other, namely Cardamino amarae-Alnetum incanae Šomšák 1961, Caltho laetae-Alnetum incanae (Zarzycki 1963) Stuchlik 1968 and Caltho laetae-Alnetum glutinosae Šomšák (1961) 1979(see also Pancer-Kotejowa 1973. The last name represents a younger homonym of the Caltho palustris-Alnetum glutinosae Šomšák 1961 (ICPN § 31) which has heterogeneous syntaxonomic content (Slezák et al 2013). The phytosociological material in original diagnoses of two remaining associations is very similar in overall floristic spectrum (Šomšák 1961, Zarzycki 1963, Stuchlik 1968).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the significant fluctuations in the groundwater table, the spatial structure of alder carr stands may be remarkably diverse and consist of two contrasting microhabitats, which are hummocks and hollows [16,17]. Hummocks are formed by adventitious roots of black alder and are elevated above the annual peak of the water table fluctuations [18].…”
Section: Introductionmentioning
confidence: 99%